Protective immunity against infectious spleen and kidney necrosis virus induced by mannose modified subunit vaccine with carbon nanotubes in mandarin fish - Zhao, Zhao; Li, Yang; Chen, Guo; Zhang, Chen; Wang, Gao‐Xue; Zhu, Bin (Aquaculture research, 2022)
Due to its wide host range and frequently causing significant mortality, infectious spleen and kidney necrosis virus (ISKNV) has caused huge economic losses on mandarin fish in China. There are no commercial drugs to cure ISKNV, and vaccines are regarded as one of the most effective measures to control virus infection. Because of the weak immunogenicity of antigen protein, subunit vaccines may require multiple booster immunizations, adjuvants or carriers to ensure strong and long‐term protective immunity. In this work, based on MCP (main capsid protein) subunit vaccine, we used single‐walled carbon nanotubes (SWCNTs) as carrier and mannose (M) as targeting factors to construct SWCNTs‐M‐MCP vaccine. After injection immunization, rapid and strong antibody titres were detected in SWCNTs‐M‐MCP groups which were significantly higher than that of MCP groups and SWCNTs‐MCP groups at the same immune doses. The antibody titre of the highest immune group (5 μg SWCNTs‐M‐MCP) reached more than 2.5 times that of the control group at 21 days postvaccination. Similar results were found in enzyme activities and immune‐related genes expression. All enzyme activities and immune‐related genes expression of 5 μg SWCNTs‐M‐MCP group at 21 days postvaccination were significantly higher than those of all dosages MCP groups and SWCNTs‐MCP groups. This study showed that SWCNTs and mannose can significantly improve the immune responses of vaccines and may provide an effective strategy against ISKNV.